Maximal values for the simultaneous number of null components of a vector and its Fourier transform - Pinos, Alberto Debernardi (Reports@SCM, 2016)
Motivated by the uncertainty principle, the purpose of this work is to find the maximal value of simultaneous number of null components of a vector and its discrete Fourier transform. In other words if we denote W and Z the number of null components of a vector x and its Fourier transform, respectively, the uncertainty principle ensures that W and Z are inversely proportional. We study the best possible balance between those two numbers.